Rough fermatean fuzzy decision-based approach for modelling IDS classifiers in the federated learning of IoMT applications - Abdullah Hussein Abdullah Al-Amoodi (Tanjung Malim, 2023)
Rough fermatean fuzzy decision-based approach for modelling IDS classifiers in the federated learning of IoMT applications by Abdullah Hussein Abdullah Al-Amoodi